2012
DOI: 10.1021/nl301555t
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-Enabled Silver Nanoantenna Sensors

Abstract: Silver is the ideal material for plasmonics because of its low loss at optical frequencies but is often replaced by a more lossy metal, gold. This is because of silver's tendency to tarnish and roughen, forming Ag(2)S on its surface, dramatically diminishing optical properties and rendering it unreliable for applications. By passivating the surface of silver nanostructures with monolayer graphene, atmospheric sulfur containing compounds are unable to penetrate the graphene to degrade the surface of the silver.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
148
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(153 citation statements)
references
References 37 publications
3
148
0
1
Order By: Relevance
“…The recent development of graphene technology also prompts the incorporation of graphene into nanoantenna design. Ag is known to suffer from sulfidation under ambient environment, resulting in degradation of the plasmonic property 136 . Graphene was shown to be able to passivate the Ag and prevent sulfidation without affecting the plasmonic property of the Ag nanoantenna 136 .…”
Section: Alternative Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent development of graphene technology also prompts the incorporation of graphene into nanoantenna design. Ag is known to suffer from sulfidation under ambient environment, resulting in degradation of the plasmonic property 136 . Graphene was shown to be able to passivate the Ag and prevent sulfidation without affecting the plasmonic property of the Ag nanoantenna 136 .…”
Section: Alternative Structuresmentioning
confidence: 99%
“…Ag is known to suffer from sulfidation under ambient environment, resulting in degradation of the plasmonic property 136 . Graphene was shown to be able to passivate the Ag and prevent sulfidation without affecting the plasmonic property of the Ag nanoantenna 136 . Additionally, radical changes in the plasmon energy and strength were also observed by electrically doping patterned graphene arrays with a gate voltage 137 .…”
Section: Alternative Structuresmentioning
confidence: 99%
“…Alternatively, recent results demonstrated that graphene layers can serve as an excellent protection against tarnishing of Ag-based plasmonic structures. 24 In comparing reflectance-based vs. ellipsometer-based parameter extraction, we find that in-plane permittivity results show excellent agreement between the two methods, while out-of-plane permittivity results do not agree as well, especially for the real part of the permittivity. The discrepancy may be based on experimental challenges of measuring out-of-plane permittivity.…”
Section: Discussionmentioning
confidence: 82%
“…However, the chemically inert, 1G-covered Ag nanoantennas did not show signs of changes; the surfaces of the particles kept their triangle shape, as shown in Figure 1e. In a previous study, by passivating the surface of silver nanostructures with 1G, atmospheric sulfur-containing compounds (hydrogen sulfide (H 2 S) and carbonyl sulfide) were unable to degrade the surface of the silver 33 . The ABNA is protected by the graphene monolayer.…”
Section: Introductionmentioning
confidence: 99%